Mapping Disinformation During the Covid-19 in Indonesia: Qualitative Content Analysis - Devie Rahmawati; Deddy Mulyana; Giri Lumakto; Mila Viendyasari; Wiratri Anindhita (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
During life-threatening situations such as the Covid-19 pandemic, disinformation is rife. While people project their affective aspects into understanding the situation, their fear of Covid-19 interferes with their logical and reasonable assessment of disinformation. Less credible information such as rumors becomes reliable for some people. This study aims to map the disinformation category based on the Ministry of Communication and Information report from January to March 2020. There are 359 hoaxes with five categories and 30 sub-categories. This study uses qualitative content analysis as a method. The study results revealed that most of the disinformation during the Covid-19 pandemic was related to the spread of hoaxes on health issues. This research implies that several recommendations are made to respond to the urgency of handling disinformation during Covid-19 in Indonesia, such as initiating digital literacy and media literacy in the national education system.